2016
DOI: 10.2463/mrms.mp.2015-0099
|View full text |Cite
|
Sign up to set email alerts
|

Juxtacortical Lesions in Multiple Sclerosis: Assessment of Gray Matter Involvement Using Phase Difference-enhanced Imaging (PADRE)

Abstract: Purpose:In multiple sclerosis (MS), a juxtacortical lesion at the border between the gray matter (GM) and subcortical white matter (WM) may often involve the GM. A recently developed, phase-weighted magnetic resonance imaging (MRI) technique “phase difference enhanced imaging (PADRE)” can delineate the GM and WM clearly due to the difference in myelin concentration. We evaluated whether PADRE is useful for the detection of GM involvement in the juxtacortical MS lesions.Methods:One neuroradiologist reviewed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…41 SWM regions have also been reported as one of the predilection sites for MS lesions. 5,42,43 Previous studies investigating SWM integrity and/or lesion load in SWM regions reported correlations between imaging metrics and cognitive performance both in healthy subjects and patient populations. 4,44,45 Since SWM structural connectivity shows a leftward bias across most of the brain, 3 language function may be selectively affected by SWM microstructural damage.…”
Section: Discussionmentioning
confidence: 99%
“…41 SWM regions have also been reported as one of the predilection sites for MS lesions. 5,42,43 Previous studies investigating SWM integrity and/or lesion load in SWM regions reported correlations between imaging metrics and cognitive performance both in healthy subjects and patient populations. 4,44,45 Since SWM structural connectivity shows a leftward bias across most of the brain, 3 language function may be selectively affected by SWM microstructural damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our lesion-by-lesion analysis demonstrated that 8 lesions rated as CMIs on SWI were rated as juxtacortical WM alone on T2WI/FLAIR, suggesting that SWI may be more accurate for assessing disease burden, especially GM involvement. In a previous study, phase-weighted MR imaging such as SWI had superior contrast between the GM and the surrounding WM, 29,30 which may contribute to improved CMI detection. However, CMIs may not be seen on T2WI/FLAIR because they can be obscured from CSF by partial volume effects.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies of PADRE reported clear demonstration of normal structures, such as small fiber tracts of the brain stem ( 13 ), layers of the optic radiation, the stria of Gennari ( 16 , 17 ), gray-to-white matter interface or SWM ( 17 19 ) and the internal structures of the thalamus ( 14 ) with TEI. In addition, the relevance of PADRE findings to aging ( 49 ) and various pathological conditions including multiple system atrophy of the cerebellar type ( 13 ), Parkinson's disease ( 50 , 51 ), amyotrophic lateral sclerosis ( 15 ), multiple sclerosis ( 52 ) and Alzheimer's disease ( 53 ) has also been reported.…”
Section: Discussionmentioning
confidence: 99%